Gambaran Pelaksanaan Senam Otak (Brain Gym) Pada Lansia di Panti Wredha Budi Dharma Yogyakarta - Etik Pratiwi (Jurnal Keperawatan Notokusumo, 2016)
Background: Demographic elderly population in the world has changed. The United Nation has predicted this population increase until 10% at 2050. The stimulation to increase the brain potential by excercice, give toys needed concentration, orientation both memory and visual. Brain gym is one of the stimulation to increase the brain potential especially at elderly. Method: This is descriptive analitic study by observe the brain gym activity at Elderly House of Budhi DharmaYogyakarta. There are 32 elderly join to this programm at March-April 2008. Result: Elderly who participate in this program consist of 27 respondents (84.37%), 19 person of them (59.37%) are female and junior high school education 11 (34.37%). The movemont of the brain performed on the elderly in this experiment is a cross-motion, 8 beds, abdominal breathing, activate the hands, feet swaying, pump betiss, horses, and muscle flexing movement. Gymnastic movements of the brain (brain gym) carried out for 1, 5 hours during one week. Conclusion: The movemont of the brain performed on the elderly in this experiment is a cross-motion, 8 beds, abdominal breathing, activate the hands, feet swaying, pump betiss, horses, and muscle flexing movement. Gymnastic movements of the brain (brain gym) carried out for 1, 5 hours during one week.